Optimization, kinetics isotherm, and reusability studies of methylene blue dye adsorption using acrylic acid grafted rubber hydrogel - Siti Fairus M. Yusoff,; Fazira Firdaus,; Nur Adly Ahmad Zahidi,; Nurul Huda Abdul Halim, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Hydrogel based on liquid natural rubber (LNR) crosslinked with acrylic acid (AAc) was synthesised and applied for the adsorption of methylene blue (MB) in aqueous solutions. The LNR/AAc hydrogel was prepared by free-radical polymerisation using potassium persulfate (KPS) and N,N-methylenebisacrylamide (MBA) as the initiator and the crosslinking agent, respectively. The effect of three variables (i.e., AAc:LNR weight ratio, KPS concentration and MBA concentration) on the hydrogel preparation for MB removal was further investigated using response surface methodology (RSM). A quadratic polynomial model with the analysis of variance (ANOVA) results yielding R2 value of 0.9833 was consequently obtained. The optimum conditions for the hydrogel preparation were identified as AAc:LNR weight ratio of 2.59 g/g, KPS concentration of 0.08 M and MBA concentrations of 0.08 M and resulting a high percentage of MB removal about 92.57% was obtained. Therefore, the kinetic and isotherm models of MB removal were represented by the pseudo-second order and Freundlich model, respectively, and reusability studies were also investigated resulting in the hydrogel can be used up to four cycles.